Studi Tentang Rendahnya Kemampuan Membaca Peserta Didik Kelas II SDN-8 Menteng Palangka Raya - Suniati Suniati (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2016)
This study aims to determine the low of students’ reading ability on the second-grade students of SDN-8 Menteng Palangka Raya. This research uses the descriptive method. The population in this study were all students of class II Which are divided into two classes: II-A and II-B are numbered, 34 people. The sample in this study is the entire study population totaling 34 students. The results of the study are the dominant factor until very low dominant of reading ability of the second-grade students of SDN-8 Menteng Palangka Raya, that students in reading did not pay attention to punctuation there are 34 students or 100%. Students do not understand the sentence he read there 32 students or 94.11%. Students do not know how to read, there are 22 people or 64.70% of students. Students in reading omit letters or words there are 22 people or 64.70% of students, and students error pronounce the letter that sounds similar to the letters b and p there are 21 students or 61.77%.